Thermal and structural modification in transparent and magnetic gallogermanate glasses induced by Gd2O3 - Zaiter, Rayan (2022)
A series of new transparent and magnetic barium gallogermanate glasses in the system (x) Gd2O3 – (100-x) [20BaO−15Ga2O3−65GeO2] with x = 0, 8, 14, 18, 22 and 25 mol% were synthesized. Their thermal, structural and magnetic properties were characterized. Based on the differential scanning calorimetry results, one determined the composition domain exhibiting the highest thermal stability toward crystallization and provided a detailed experimental fabrication method for the production of optical fibers. The local glass structure investigated using combined Raman and Infrared vibrational spectroscopies shows a progressive depolymerization of the 3D glass germanate network accompanied with an increase of non-bridging oxygens when increasing the Gd2O3 content. The incorporation of gadolinium ions tends to extend the IR transmission window. Thanks to the magnetic susceptibility measurements, the paramagnetic behavior was evidenced, and increases with the Gd3+ content. The combination of the optical, thermal and magnetic properties of Gd2O3 gallogermanate glasses as well as their ability to be shaped into optical fibers make them promising materials for their integration in MIR functional optical components.